2010
DOI: 10.1523/jneurosci.5377-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Spinal Microglial P2X7 Receptor in Generation of Tolerance to Morphine Analgesia in Rats

Abstract: Morphine loses analgesic potency after repeated administration. The underlying mechanism is not fully understood. Glia are thought to be involved in morphine tolerance, and P2X 7 purinergic receptor (P2X 7 R) has been implicated in neuron-glia communication and chronic pain. The present study demonstrated that P2X 7 R immunoreactivity was colocalized with the microglial marker OX42, but not the astrocytic marker GFAP, in the spinal cord. The protein level of spinal P2X 7 R was upregulated after chronic exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
102
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(108 citation statements)
references
References 38 publications
4
102
2
Order By: Relevance
“…4 for summary) have also been observed using immunohistochemistry for CD11b (Holdridge et al, 2007;Hutchinson et al, 2009a;Agostini et al, 2010;Mattioli et al, 2010) and ionized calcium binding adaptor molecule-1 (Iba1) Horvath et al, 2010b;Zhou et al, 2010) and confirmed with Western (Mika et al, 2009) and mRNA analysis (Raghavendra et al, 2004a;Tawfik et al, 2005;Cao et al, 2010). Again, significant regional heterogeneity was observed; morphine-induced decreases in CD11b expression were reported in the cornu ammonis of the hippocampus, nucleus accumbens, and substantia nigra, and no change was reported in the dorsal raphe nucleus and medial prefrontal cortex (Hutchinson et al, 2009a).…”
Section: Adaptations In Non-neuronal Cell Marker and Reactivity Phenomentioning
confidence: 72%
See 2 more Smart Citations
“…4 for summary) have also been observed using immunohistochemistry for CD11b (Holdridge et al, 2007;Hutchinson et al, 2009a;Agostini et al, 2010;Mattioli et al, 2010) and ionized calcium binding adaptor molecule-1 (Iba1) Horvath et al, 2010b;Zhou et al, 2010) and confirmed with Western (Mika et al, 2009) and mRNA analysis (Raghavendra et al, 2004a;Tawfik et al, 2005;Cao et al, 2010). Again, significant regional heterogeneity was observed; morphine-induced decreases in CD11b expression were reported in the cornu ammonis of the hippocampus, nucleus accumbens, and substantia nigra, and no change was reported in the dorsal raphe nucleus and medial prefrontal cortex (Hutchinson et al, 2009a).…”
Section: Adaptations In Non-neuronal Cell Marker and Reactivity Phenomentioning
confidence: 72%
“…Increased microglial expression of other cell surface receptors such as CCR5 (Li et al, 2002;Bokhari et al, 2009), TLR2 , TLR4 (Hutchinson et al, 2008a), P2X4 (Horvath and DeLeo, 2009), and P2X7 (Zhou et al, 2010) have also been reported after opioid exposure. These opioid-induced adaptations in CNS-immune cell receptor expression are accompanied by profound changes in astrocyte and microglial cellular morphology (Holdridge et al, 2007), with the total length of NEUROIMMUNOPHARMACOLOGIC IMPLICATIONS FOR OPIOID ANALGESIA astrocytes altered in a regional specific fashion (Lazriev et al, 2001).…”
Section: Adaptations In Non-neuronal Cell Marker and Reactivity Phenomentioning
confidence: 95%
See 1 more Smart Citation
“…siRNA targeting rat P2X7R mRNA P2X7 small interfering RNA (siRNA) was synthesized according to the four sense sequences shown in a previous study [15]: (1) GUACA GUGGCUUCAAGU AU, (2) GGAUGGACCCACAAAGU AA, (3) UUACAGAGGUGGCAGUU CA, (4) GAACGAU GUCUUUCAGUAU. SiGENOME RISC-Free control siRNA was used as non-targeting control.…”
Section: Methodsmentioning
confidence: 99%
“…In line with this view, many compounds, which modify microglial functions successfully, alleviate neuropathic pain in experimental models (Toda et al, 2011). Microglia also seem to be involved in the ethanol-induced neuropathic pain-like state in the rat (Narita et al, 2007) and could play a role in the development of pain following chronic exposure to opioids (Horvath et al, 2010; Zhou et al, 2010). Black and Waxman discuss sodium channels and microglial function in their article of this Special issue and demonstrate that blocking sodium channels significantly attenuates several effector functions of microglia activated by exposure to ATP and LPS, supporting a role for sodium channel activity in the molecular pathways governing microglial activation.…”
Section: Introductionmentioning
confidence: 96%